2013
DOI: 10.1002/jmv.23484
|View full text |Cite
|
Sign up to set email alerts
|

Impact of influenza virus escape‐mutations on influenza detection by the rapid influenza diagnostic test

Abstract: During the influenza pandemic of 2009-2010, rapid influenza diagnostic tests (RIDTs) were used to detect influenza viral infections because they are quick and simple to use. However, retrospective studies showed that RIDTs performed poorly when used to diagnose pandemic viral infections. Determining how amino acid sequence changes in pandemic or epidemic influenza viral antigens impact clinical value of RIDTs has not been possible, because the viral epitopes recognized by RIDTs have been not mapped. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Rudneva et al (2012) also generated H1N1pdm09 specific mAbs (5F7 and 6A3), and it was demonstrated that escape-mutants generated by immune pressure of the mAbs have HA G172E substitution. As previously mentioned, immunological pressure by our mAb-D383 also generated HA G172E escape-mutation on the HA of the H1N1pdm09 virus (Yi et al, 2013). Reversegenetics experiments showed that a single G172E HA on the Sa site of HA was sufficient to escape from sera isolated from ferrets infected with an H1N1pdm09 strain (A/California/ 07/2009).…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Rudneva et al (2012) also generated H1N1pdm09 specific mAbs (5F7 and 6A3), and it was demonstrated that escape-mutants generated by immune pressure of the mAbs have HA G172E substitution. As previously mentioned, immunological pressure by our mAb-D383 also generated HA G172E escape-mutation on the HA of the H1N1pdm09 virus (Yi et al, 2013). Reversegenetics experiments showed that a single G172E HA on the Sa site of HA was sufficient to escape from sera isolated from ferrets infected with an H1N1pdm09 strain (A/California/ 07/2009).…”
Section: Discussionmentioning
confidence: 85%
“…4B) compared with those of 1918 H1N1 and 2009 H1N1 viral HAs. Also, the amino acid sequences corresponding to the residues of the HA close-up views shown In the blue Sa antigenic sites, G172E, P176Q, and K180E mutation sites that were elicited as escape-mutation sites to the mAb-D383 in our previous study (Yi et al, 2013) are highlighted in yellow. In the purple F' subdomains, the G56E mutation site that was elicited as an escape-mutation site from mAb-I38 is marked in green.…”
Section: Fig 3 Reactivity Of the Mabs (I38 And D383) To Escape-mutamentioning
confidence: 99%
See 3 more Smart Citations